PERFORMANCE OF NI3AL AND TIO2 COATINGS ON T22 BOILER TUBE STEEL IN SIMULATED BOILER ENVIRONMENT IN LABORATORY (Journal of Mechanical Engineering, 2017)
The corrosion of boiler steel tube in coal fired boiler is main matter during design and operation of thermal power plant and it leads to both direct and indirect cost and energy lost, including losses due to plant shut down time and inefficiency of operation. One of the feasible solution to solve the problem is providing surface coating on boiler steel tube, which on one hand protect the tube from highly corrosive flue gaseous and on other hand increase their operating life. Ni3Al and TiO2 and coatings were sprayed on ASTM SA213-T22 steel by using the HVOF process. Hot corrosion studies were conducted on the uncoated as well as coated sprayed specimens in molten salt environment of Na2SO4-60%V2O5 at 900ºC for 50 cycles. In the experiment each cycle consist of 1 hr of heating in tube furnace followed by 20 minute of cooling in air. The thermo-gravimetric technique was used in order to establish the kinetics of corrosion. XRD, SEM/EDS testing were used to examine the corrosion specimens. Theresult shows that both the coated samples are beneficial to corrosion resistance over uncoated samples. TiO2 coating was found to be most protective followed by the Ni3Al coating.